Alpha 3 ganglionic acetylcholine receptor antibody associated refractory status epilepticus. (February 2016) - Bansal, Poonam; Zutshi, Deepti; Suchdev, Kushak; Azher, Idrees; Mohamed, Wazim
Highlights: Autoimmune seizures linked to Alpha 3 ganglionic acetylcholine receptor autoantibody. The patient presented with new onset refractory status epilepticus. Immunotherapy with steroids was successful. The diagnosis of autoimmune epilepsy requires a high level of suspicion.